Topics in arithmetic and determinacy - Mendes da Silva Maia, NF (2023)
This thesis is about Arithmetical Determinacy. Loosely, this is the problem of whether every question in arithmetic has a determinate answer. In this work I discuss how to exactly understand the concept of determinacy, I criticise arguments for and against the claim that arithmetic is determinate, and examine how questions about determinacy may be applied to other debates in the philosophy of mathematics.